A conceptual model of demand chain management. (1st January 2013) - Varkhedkar, Narendra; Seth, Nitin; Verma, Prakash
The demand chain management (DCM) involves a high level of complexity due to interrelationships and feedback nature of process parameters, which makes the system dynamic. Understanding these dynamics will help in better management of the demand chain. The scope of DCM is not limited to fulfillment of present demand but also extends to managing the demand creation, which requires involvement of the whole enterprise, and to accomplish this it is necessary to take into consideration all the complexities and dynamics involved within the system. The purpose of this paper is to present a conceptual model of demand chain management, and suggest a mechanism for processing of demand information, which will help in developing an understanding of complexities and feedback nature. Exploratory interviews were conducted with experts to identify the drivers of DCM and to understand the impact of demand information in decision making. The conceptual model presented shows parameters affecting the DCM. It will be useful in developing an understanding of complexities and dynamics involved in DCM. The understanding thus gained will result in improvement of DCM effectiveness, making it more responsive and customer-oriented. Further, the paper also attempts to address research implications for future research in this area.